The Lyapunov Exponents of Reversible Cellular Automata Are Uncomputable - Kopra J. (Switzerland, 2022)
We will show that the class of reversible cellular automata (CA) with right Lyapunov exponent 2 cannot be separated algorithmically from the class of reversible CA whose right Lyapunov exponents are at most 2−δ for some absolute constant δ>0. Therefore there is no algorithm that, given as an input a description of an arbitrary reversible CA F and a positive rational number ϵ>0, outputs the Lyapunov exponents of F with accuracy ϵ.
Unconventional Computation and Natural Computation : 18th International Conference, UCNC 2019, Tokyo, Japan, June 3–7, 2019, Proceedings